A Strategic Communication Approach to Youth Engagement in Transitional Justice in Post-Insurgency Yobe State, Nigeria - Ibrahim, Adamkolo; Muhammad, Usman Adamu; Ibrahim, Abubakar Tijjani (PT Agung Media Publisher, 2025)
The Boko Haram insurgency has inflicted profound disruption on communities in northeast Nigeria, with Gujba Local Government Area (LGA) among the most severely affected. Although transitional justice (TJ) initiatives have been introduced to address human rights violations, youth participation has remained limited and largely symbolic. This article examines the specific roles that young people occupy in TJ processes in Gujba LGA and proposes a strategic communication framework to enhance their substantive engagement. A mixed methods design was employed, with quantitative data from a structured survey of 300 youths (187 male, 113 female) and qualitative insights drawn from 13 key informant interviews. Findings reveal that while 40% of respondents have ever attended TJ events, attendance is typically confined to community reconciliation (60%), with minimal involvement in policy workshops (25%). Youth contributions frequently remain logistical or testimonial rather than consultative. Demographic analysis indicates higher participation among those aged 20–24 and individuals with post-secondary education, whereas farmers and young women face pronounced barriers. Drawing on framing and diffusion theories, the article outlines a seven-step advocacy campaign encompassing tailored messages in local languages, multi-channel dissemination (radio, town criers, mobile messaging) and culturally sensitive formats (women only sessions, youth led media). Preliminary pilot data suggest that targeted messaging can raise awareness from 35% to over 60% and increase active speaking roles among participants by 30%. The proposed framework offers policymakers and practitioners a replicable model for transforming youth from passive observers to active stakeholders in TJ, thereby strengthening the legitimacy and effectiveness of post conflict recovery processes.